Penerapan Model Project Based Learning untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa Sekolah Dasar pada Pembelajaran IPAS: Systematic Review - M. Agung Alwanda (Advances In Education Journal, 2025)
The low level of creative thinking skills among elementary school students in science, technology, engineering, and mathematics (STEM) learning is a major challenge in implementing the Merdeka Curriculum. This study aims to examine the application of the Project-Based Learning (PjBL) model in improving students' creative thinking skills through a PRISMA-based Systematic Literature Review (SLR) of 22 articles published between 2020 and 2025. Data were collected through systematic searches on Google Scholar and analyzed descriptively and narratively. The results showed that PjBL was effective (45.5%) to very effective (50%) in developing students' creativity, courage to express opinions, and ability to design solutions. The dominant research methods were quasi-experiments (55%) and action research (36%), with general science, local culture, and the environment as the most frequently used themes. These findings indicate that PjBL is a relevant, contextual pedagogical approach that supports 21st-century skills.